Influence Of Media Storage Sand And Plastic Seeds With The Provision Of Cooling Water To Over Change In Quality Of Kepok Banana (Musa Normalis L) - Artamy Maulia Ikhsan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
Banana is a climacteric fruit is fruit that will perpetuate the process of maturity even though it has been harvested and is followed by the process of damage due to perpetuate fruit respiration and metabolic processes. The process of respiration in the fruit will result in rapid fruit mature and over-mature. This is an obstacle in maintaining the shelf life of a banana. This Study aims to determine the effect of storage media of sand and plastic seeds to changes in the quality of banana fruit. Storage media used in this study were sand and plastic seeds. While the banana varieties used in this study is kepok banana (Musa Normalis L). In this study each of the bunches of banana inserted into the aluminum tube that has been filled with a store media and cooling water on the outside of the storage media with high cooling water height of 10 cm from the media store. The results showed that colour of kepok banana changed from the begining until the end of storage.  Weight of kepok banana decreased by 12,45% and levels of violence decreased by 2,95 kg.s/mm on last day of storage.  In addition, the level sweetness of kepok banana increased to 23,0ºbrix and level of fruit water to 77,8% on last day of storage. Kepok banana stored in the sand has a longer shelf life (17 days) than the bananas that are stored in the storage media of plastic seeds (14 days) and control (10 days). Keywords: Storage, kepok banana, store media of sand, store media of plastic seeds, and cooling water.